High Temperature Erosion-Oxidation Mechanisms, Maps and Models - Wellman, R. G.; Nicholls, John R. (Elsevier Science B.V., Amsterdam., 2004)
The aim of this paper is to provide an overview of erosion-oxidation studies by reviewing the work that has been done on mechanisms, maps and models. High temperature erosionoxidation is a major cause of wear in both fluidised bed combustors and gas turbines and much effort has been put into understanding the phenomena and reducing wear rates. A number of different erosion-oxidation mechanisms have been proposed over the years to describe the different wear regimes, some of these mechanisms are discussed in this paper, as well as the mapping techniques that have been used to quantify wastage rates. Finally, erosion-oxidation modelling is discussed, starting with models that combine oxidation kinetics with erosion rate equations that lead to predictive models before concentrating on Monte Carlo modelling methods.